Right atrial thrombus associated with subclavian catheter developed due to total parenteral nutrition application - Kabukcu, Hanife Karakaya; Sahin, Nursel; Basarici, Ibrahim; Erbasan, Ozan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Central venous catheterization as a frequent routine clinical procedure may have significant complications. Mechanical complications may occur during catheter placement, whereas thromboembolic and infectious complications can be seen during follow-up. Total parenteral nutrition (TPN) associated central venous catheterizations may result in early mechanical complications and thrombotic and infectious complications in the long term. This paper describes a patient diagnosed as mitochondrial neurogastrointestinal encephalomyopathy requiring long-term central venous catheterization for TPN implementation, who had an infected thrombus on the catheter tip resected by cardiac surgery.